VARIASI BAHASA DAN PEMERTAHANAN BAHASA OLEH LESSOR DI KAWASAN WISATA PELABUHAN RATU - Anggel Lika Tiana; Isma Nurrahma; Najma Sahla Latifah; Reisya Amalia Irawan; Rizka Aulia Hidayah; Sofia Yanifah; Nunung Sitaresmi (Universitas Islam Malang, 2025)
This study examines language variation in rental transactions between tourists and boat lessors at Pelabuhan Ratu Beach and explores the maintenance of local languages. Using a qualitative approach with documentation and interview methods, the study found that: (1) lessors adjust their language use according to the tourists' backgrounds, (2) there are differences in language use when interacting with local versus international tourists, and (3) the maintenance of local languages remains strong in daily activities, although it is less dominant in transactional contexts. These findings highlight the importance of linguistic adaptability in tourism services while emphasizing efforts to preserve local languages.